2022
DOI: 10.3390/life12020311
|View full text |Cite
|
Sign up to set email alerts
|

PHILOS Synthesis for Proximal Humerus Fractures Has High Complications and Reintervention Rates: A Systematic Review and Meta-Analysis

Abstract: Purpose: The aim of this study was to quantify the rate of complications and reinterventions in patients treated with PHILOS plate for proximal humerus fractures (PHFs) synthesis. Methods: A comprehensive literature search was performed on the PubMed, Web of Science, Embase, and Cochrane databases up to 7 October 2021. Studies describing medium and long-term complications in PHF synthesis using the PHILOS plate were included. A systematic review and meta-analysis were performed on complications and causes of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
13
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 69 publications
0
13
0
2
Order By: Relevance
“…Erasmo et al did a study on 82 cases of proximal humerus fractures treated with PHILOS plating over a period of 4 years and found that 12% cases under went avascular necrosis. 23 27 The different functional outcomes of our study to other studies are enumerated in (Table 5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Erasmo et al did a study on 82 cases of proximal humerus fractures treated with PHILOS plating over a period of 4 years and found that 12% cases under went avascular necrosis. 23 27 The different functional outcomes of our study to other studies are enumerated in (Table 5).…”
Section: Discussionmentioning
confidence: 99%
“…International Journal of Research in Orthopaedics | May-June 2023 | Vol 9 | Issue 3 Page 557proximal humerus fractures 27. According to the Oldrini et al meta-analysis, functional outcomes were excellent in 3 studies (7.7%), good in 21 (53.8%), moderate in 13 studies (33.4%), and poor in 2 studies (5.1%).…”
mentioning
confidence: 99%
“…We read the paper published by Oldrini, L.M. et al (2022) [ 1 ] with great interest. The paper is a systematic review and meta-analysis addressing a crucial topic regarding the complications and reinterventions in patients who have been surgically treated with PHILOS plates for proximal humerus fracture fixation.…”
mentioning
confidence: 99%
“…Thank you for the opportunity to respond to the commentary [ 1 ] on our recent article “PHILOS Synthesis for Proximal Humerus Fractures Has High Complications and Reintervention Rates: A Systematic Review and Meta-Analysis” [ 2 ]. We read the commentary with much interest, and we are happy to address all the issues posed.…”
mentioning
confidence: 99%